Designing magnetic superlattices that are composed of single domain nanomagnets - Forrester, Derek M.; Kusmartsev, Feodor V.; Kovács, Endre (Beilstein Journal of Nanotechnology, 2014)
Background: The complex nature of the magnetic interactions between any number of nanosized elements of a magnetic superlattice can be described by the generic behavior that is presented here. The hysteresis characteristics of interacting elliptical nanomagnets are described by a quasi-static method that identifies the critical boundaries between magnetic phases. A full dynamical analysis is conducted in complement to this and the deviations from the quasi-static analysis are highlighted. Each phase is defined by the configuration of the magnetic moments of the chain of single domain nanomagnets and correspondingly the existence of parallel, anti-parallel and canting average magnetization states.Results: We give examples of the phase diagrams in terms of anisotropy and coupling strength for two, three and four magnetic layers. Each phase diagrams character is defined by the shape of the magnetic hysteresis profile for a system in an applied magnetic field. We present the analytical solutions that enable one to define the “phase” boundaries between the emergence of spin-flop, anti-parallel and parallel configurations. The shape of the hysteresis profile is a function of the coupling strength between the nanomagnets and examples are given of how it dictates a systems magnetic response. Many different paths between metastable states can exist and this can lead to instabilities and fluctuations in the magnetization.Conclusion: With these phase diagrams one can find the most stable magnetic configurations against perturbations so as to create magnetic devices. On the other hand, one may require a magnetic system that can easily be switched between phases, and so one can use the information herein to design superlattices of the required shape and character by choosing parameters close to the phase boundaries. This work will be useful when designing future spintronic devices, especially those manipulating the properties of CoFeB compounds.
Keywords: hysteresis; nanoparticles; magnetic phases; superlattices

(untitled) - Imre, A.; Csaba, G.; Ji, L.; Orlov, A.; Bernstein, G. H.; Porod, W. (Science, 2006)

(untitled) - Kubota, H.; Fukushima, A.; Yakushiji, K.; Yakata, S.; Yuasa, S.; Ando, K.; Ogane, M.; Ando, Y.; Miyazaki, T. (J. Appl. Phys., 2009)

(untitled) - Wu, K.-M.; Huang, C.-H.; Wang, Y.-H.; Kao, M.-J.; Tsai, M.-J.; Wu, J.-C.; Horng, L. (J. Appl. Phys., 2007)

(untitled) - Hashimoto, A.; Saito, S.; Omori, K.; Takashima, H.; Ueno, T.; Takahashi, M. (Appl. Phys. Lett., 2006)

(untitled) - Fernández-Pacheco, A.; Petit, D.; Mansell, R.; Lavrijsen, R.; Lee, J.-H.; Cowburn, R. P. (Phys. Rev. B, 2012)

(untitled) - Dediu, V. I.; Kabanov, V. V.; Sidorenko, A. S. (Phys. Rev. B, 1994)

(untitled) - Lee, K. C.; Erb, U. (Beilstein J. Nanotechnol., 2013)

(untitled) - Hu, W.; Wilson, R. J.; Koh, A.; Fu, A.; Faranesh, A. Z.; Earhart, C. M.; Osterfeld, S. J.; Han, S.-J.; Xu, L.; Guccione, S.; Sinclair, R.; Wang, S. X. (Adv. Mater., 2008)

(untitled) - Huang, J. C. A.; Hsu, C. Y.; Chen, S. F.; Liu, C. P.; Liao, Y. F.; Lin, M. Z.; Lee, C. H. (J. Appl. Phys., 2007)

(untitled) - Serantes, D.; Baldomir, D.; Pereiro, M.; Hernando, B.; Prida, V. M.; Sánchez-Llamazares, J. L.; Zhukov, A.; González, J. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Vargas, P.; Altbir, D.; Knobel, M.; Laroze, D. (Europhys. Lett., 2002)

(untitled) - Prida, V. M.; Vega, V.; Serantes, D.; Baldomir, D.; Ilyn, M.; Zhukov, A. P.; González, J.; Hernando, B. (Phys. Status Solidi A, 2009)

(untitled) - Serantes, D.; Baldomir, D.; Pereiro, M.; Arias, J. E.; Mateo-Mateo, C.; Buján-Núñez, M. C.; Vázquez-Vázquez, C.; Rivas, J. (J. Non-Cryst. Solids, 2008)

(untitled) - Roy, K.; Bandyopadhyay, S.; Atulasimha, J.; Munira, K.; Ghosh, A. W. (arXiv:1107.0387v2 [cond-mat.mes-hall], 2011)

(untitled) - Forrester, D. M.; Kusmartsev, F. V.; Kovács, E. (Phys. Rev. B, 2013)

(untitled) - Kong, Y. C.; Lim, S. H.; Lee, K.-J. (J. Korean Phys. Soc., 2009)

(untitled) - Ruderman, M. A.; Kittel, C. (Phys. Rev., 1954)

(untitled) - Kasuya, T. (Prog. Theor. Phys., 1956)

(untitled) - Yosida, K. (Phys. Rev., 1957)

(untitled) - Lai, R.; Sievers, A. (J. Appl. Phys., 1998)

(untitled) - Chen, A. P.; Zhukov, A.; González, J.; Domínguez, L.; Blanco, J. M. (J. Appl. Phys., 2006)

(untitled) - Forrester, D. M.; Kusmartsev, F. V. (Phys. Status Solidi A, 2014)

(untitled) - Ostler, T. A.; Barker, J.; Evans, R. F. L.; Chantrell, R. W.; Atxitia, U.; Chubykalo-Fesenko, O.; El Moussaoui, S.; Le Guyader, L.; Mengotti, E.; Heyderman, L. J.; Nolting, F.; Tsukamoto, A.; et al. (Nat. Commun., 2012)

(untitled) - Forrester, D. M.; Kürten, K. E.; Kusmartsev, F. V. (Phys. Rev. B, 2007)

(untitled) - Lavrijsen, R.; Lee, J.-H.; Fernández-Pacheco, A.; Petit, D. C. M. C.; Mansell, R.; Cowburn, R. P. (Nature, 2013)

(untitled) - Prida, V. M.; García, J.; Iglesias, L.; Vega, V.; Görlitz, D.; Nielsch, K.; Díaz-Barriga-Castro, E.; Mendoza-Reséndez, R.; Ponce, A.; Luna, C. (Nanoscale Res. Lett., 2013)

(untitled) - Tsai, W.-F.; Huang, C.-Y.; Chang, T.-R.; Lin, H.; Jeng, H.-T.; Bansil, A. (Nat. Commun., 2013)

(untitled) - Maassen, J.; Ji, W.; Guo, H. (Nano Lett., 2011)

(untitled) - van ’t Erve, O. M. J.; Friedman, A. L.; Cobas, E.; Li, C. H.; Robinson, J. T.; Jonker, B. T. (Nat. Nanotechnol., 2012)

(untitled) - El Mel, A.-A.; Duvail, J.-L.; Gautron, E.; Xu, W.; Choi, C.-H.; Angleraud, B.; Granier, A.; Tessier, P.-Y. (Beilstein J. Nanotechnol., 2012)

(untitled) - Kurlyandskaya, G. V.; Sánchez, M. L.; Hernando, B.; Prida, V. M.; Gorria, P.; Tejedor, M. (Appl. Phys. Lett., 2003)